2020
DOI: 10.1111/prd.12341
|View full text |Cite
|
Sign up to set email alerts
|

Sustained‐release delivery of antimicrobial drugs for the treatment of periodontal diseases: Fantasy or already reality?

Abstract: Periodontal diseases are prevalent in humans. Conventional means of combating these diseases involve basic oral hygiene, mostly toothbrushing, use of mouthwashes, and flossing. Supplementary means of treatment, either clinical or pharmaceutical, are often necessary. The use of sustained‐release delivery systems, applied locally to the periodontal pocket, seems to be one feasible approach: local sustained‐release delivery of antibacterial agents to treat periodontal diseases is conceivable. The use of local (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 91 publications
(98 reference statements)
0
27
0
Order By: Relevance
“…In addition, Oxaliplatin also has certain neurotoxicity, and even triggers symptoms such as numbness in the end of hands and feet in patients ( 21 ). As research has progressed, studies have shown that drug carrier-mediated delivery alters drug distribution in human, affects local concentrations by controlling the rate of drug release, or targets drug transport to patient foci ( 22 ). MSN has been extensively adopted as a promising drug delivery material over the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Oxaliplatin also has certain neurotoxicity, and even triggers symptoms such as numbness in the end of hands and feet in patients ( 21 ). As research has progressed, studies have shown that drug carrier-mediated delivery alters drug distribution in human, affects local concentrations by controlling the rate of drug release, or targets drug transport to patient foci ( 22 ). MSN has been extensively adopted as a promising drug delivery material over the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…The periodontal pocket, due to its anatomy, although variable, is a very good site for local delivery of the drug, whose distribution is also facilitated by the crevicular fluid. Drug delivery systems that mold into the particular pocket shape improve bioavailability by encompassing all pocket areas [35]. Therefore, when comparing systemic versus local delivery systems, the latter possess a few advantages, such as a targeted minimal and direct application at the infection site, dose and frequency of administration cutback, gastrointestinal evasion and first pass metabolism, the enhanced compliance of patients and incorporation of additional non-systemically deliverable agents (e.g., chlorhexidine) [36].…”
Section: Systemic Administration Of Antibiotics In Periodontal Therapymentioning
confidence: 99%
“…In recent years, nanostructured polymeric fibers have been developed in order to enhance the efficacy of the drugs at the application site [171]. The advantages of nanofibers involve large surface area, high porosity, and high mechanical strength which make it a potential candidate for the application into the periodontal pocket [172]. Electrospinning technique is the mostly used method for the production of nanofibers, which allows adjustment of fiber size, drug loading, and mechanical properties can be adjusted [173].…”
Section: Strips/fibersmentioning
confidence: 99%